Increased Expression of UMAMIT Amino Acid Transporters Results in Activation of Salicylic Acid Dependent Stress Response - Besnard, Julien; Sonawala, Unnati; Maharjan, Bal; Collakova, Eva; Finlayson, Scott A.; Pilot, Guillaume; McDowell, John; Okumoto, Sakiko (Frontiers in Plant Science, 2021)
In addition to their role in the biosynthesis of important molecules such as proteins and specialized metabolites, amino acids are known to function as signaling molecules through various pathways to report nitrogen status and trigger appropriate metabolic and cellular responses. Moreover, changes in amino acid levels through altered amino acid transporter activities trigger plant immune responses. Specifically, loss of function of major amino acid transporter, over-expression of cationic amino acid transporter, or over-expression of the positive regulators of membrane amino acid export all lead to dwarfed phenotypes and upregulated salicylic acid (SA)-induced stress marker genes. However, whether increasing amino acid exporter protein levels lead to similar stress phenotypes has not been investigated so far. Recently, a family of transporters, namely USUALLY MULTIPLE ACIDS MOVE IN AND OUT TRANSPORTERS (UMAMITs), were identified as amino acid exporters. The goal of this study was to investigate the effects of increased amino acid export on plant development, growth, and reproduction to further examine the link between amino acid transport and stress responses. The results presented here show strong evidence that an increased expression of UMAMIT transporters induces stress phenotypes and pathogen resistance, likely due to the establishment of a constitutive stress response via a SA-dependent pathway.